PENGGUNAAN MEDIA GAMBAR PUTAR PADA PROSES PEMBELAJARAN BAHASA DI TKM NU 134 HIDAYATUL UMMAH BALONGPANGGANG GRESIK - Riyadlotus Sholichah; Nur Kholifah (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2021)
Aspects of language development is an important ability in the growth and development of children. Not all children aged 5-6 years are able to achieve very well developed indicators in language development. This encourages teachers to use learning media so that children's language skills can improve. The teacher applies the use of rotating image media in language learning. This research includes qualitative descriptive research. The purpose of this study was to determine the use of rotating image media in language learning in group B TKM NU 134 Hidayatul Ummah. The results showed that out of 47 children, children who met the achievement of indicators were at the BSB level (Developing Very Well), namely 18 and BSH (Developing According to Expectations) as many as 19. However, there were 10 children who did not meet the achievement indicators, so how many at the MB level (Starting from Develop). From these data, it can be concluded that the use of rotating image media in the language learning process at TKM NU 134 Hidayatul Ummah is quite effective because most of the children are enthusiastic and meet the achievement indicators.